2021
DOI: 10.1016/j.redox.2021.102074
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of cannabidiol on the membrane proteins of skin keratinocytes exposed to hydrogen peroxide via participation in the proteostasis network

Abstract: Hydrogen peroxide (H 2 O 2 ) is widely used in clinical practice due to its antiseptic properties and its ability to heal wounds. However, due to its involvement in the formation of ROS, H 2 O 2 causes several side effects, including disorders of the metabolism of skin cells and the development of chronic inflammation mediated by oxidative stress. Therefore, this study evaluated the effects of cannabidiol (CBD), a phyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 86 publications
1
9
0
Order By: Relevance
“…This situation demonstrates the importance of CBD's regulatory effect on the proteasomal degradation of Nrf2 which is a critical part of the regulation of Nrf2 activity. This may confirm that the regulatory effect of CBD on the proteostasis network has been demonstrated by CBD-mediated protection in the expression and oxidative modifications of proteins involved in proteasome activity and protein folding [ 24 ]. Moreover, several studies show the CBD-mediated regulation of p62 expression in both an increasing [ 69 ] and decreasing trend [ 70 ], in Sprague Dawley rats using CBD (100 mg/kg) [ 69 ] and in Sprague Dawley rats with hemorrhagic shock-induced brain injury using this phytocannabinoid (5 mg/kg) [ 70 ], respectively.…”
Section: The Modulatory Activity Of Cannabidiol With Respect To the N...supporting
confidence: 67%
See 2 more Smart Citations
“…This situation demonstrates the importance of CBD's regulatory effect on the proteasomal degradation of Nrf2 which is a critical part of the regulation of Nrf2 activity. This may confirm that the regulatory effect of CBD on the proteostasis network has been demonstrated by CBD-mediated protection in the expression and oxidative modifications of proteins involved in proteasome activity and protein folding [ 24 ]. Moreover, several studies show the CBD-mediated regulation of p62 expression in both an increasing [ 69 ] and decreasing trend [ 70 ], in Sprague Dawley rats using CBD (100 mg/kg) [ 69 ] and in Sprague Dawley rats with hemorrhagic shock-induced brain injury using this phytocannabinoid (5 mg/kg) [ 70 ], respectively.…”
Section: The Modulatory Activity Of Cannabidiol With Respect To the N...supporting
confidence: 67%
“…Also, another study in human umbilical vein endothelial cells demonstrated a significant increase in the level of HMOX1 mRNA and protein together with Nrf2 level caused by CBD action [ 17 ]. Moreover, CBD intervention to prevent excessive production of ROS protects cell metabolism against oxidative damage of other macromolecules such as lipids [ 22 , 23 ] and proteins leading to the maintenance of protein homeostasis [ 24 ] which are the critical targets for oxidative damages-associated pathology [ Fig. 1 ].…”
Section: Cannabidiol a Natural Compound Interfering With Redox Balancementioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, research on the effectiveness of the pharmacological action of phytocannabinoids is related to the assessment of the independent impact of these compounds on skin cells, as well as the effects after UV irradiation (in vitro or ex vivo examinations) on skin cells, or during its direct exposure to the skin (in vivo studies) [ 52 , 53 , 54 , 55 ]. The skin is also exposed to chemical agents (e.g., disinfectants such as hydrogen peroxide) and pathogens (bacteria/viruses) [ 56 , 57 ]. Exposing the skin/skin cells to the above-mentioned physicochemical and biological factors usually leads to oxidative stress and inflammation in the skin cells, which may result in pathological changes and the development of skin diseases [ 58 , 59 ].…”
Section: Effect Of Phytocannabinoids On Skinmentioning
confidence: 99%
“…[17] Besides, CBD could partially prevented the changes of the keratinocyte membranes proteome via maintaining proteostasis networks and reducing oxidative stress. [18] However, there is a lack of systematic studies about the antioxidant capacity of CBD at the cellular level and the molecular mechanism also remains to be elucidated. H 2 O 2 -induced oxidative damage model is one of the most commonly used cell models of oxidative stress, which can be employed to evaluate the antioxidant effect of active components at the cellular level.…”
Section: Introductionmentioning
confidence: 99%